Allying to Kill: Terrorist Intergroup Cooperation and the Consequences for Lethality. (March 2014) - Horowitz, Michael C.; Potter, Philip B. K.
Terrorist organizations do not operate in isolation. Instead, they forge alliances with one another, which generate a tight network of intergroup relationships. We argue that these relationships serve to increase group capacity, manifesting itself in the ability of a group to conduct deadly attacks. However, groups are notably judicious when they forge these cooperative ties, preferring to link to the strongest groups to which they have access. The result of this process of preferential attachment is a core/periphery structure in the broader network of alliances. Moreover, groups with ties to organizations at the core of the broader universe of relationships reap more rewards than those with large numbers of less meaningful alliances. Terrorism research and counterterrorism policy should assess terrorist organizations in the broader context of their interrelationships and depth of alliances rather than in isolation.